Comparative study on surgical outcomes between laparoscopic and open cornuotomy in urban tertiary center of Malaysia - Wan Ahmad Hazim Wan Ghazali; Nurul Huda Zainal Abidin; Aisyah Munirah Muda; Habibah Abdul Hamid (Gynecology and Minimally Invasive Therapy, 2018)
Study Objective: The objective of the study was to evaluate the prevalence of interstitial ectopic pregnancy and to compare the surgical outcomes of laparoscopic cornuotomy (LC) and laparotomy (open) cornuotomy (OC) of cornual ectopic pregnancy and to analyze its associated factors. Materials and Methods: A cross-sectional study was conducted involving cases of interstitial ectopic in Hospital Putrajaya, Putrajaya, Malaysia, over a 10-year period (2005–2014). Data on sociodemographic, clinical profile, perioperative, and postoperative were obtained from the electronic medical records. Measurement and Main Results: The prevalence of cornual pregnancy was 4.0% (n = 14) out of total 347 cases of all ectopic pregnancies in Putrajaya Hospital. The mean ± standard deviation age of patient in the LC group and OC group was 29.3 ± 5.9 years and 31.4 ± 7.3 years, respectively. The duration of hospitalization and mean operating time were both significantly shorter in the LC group than in the OC group (1.43 ± 0.54 versus 2.57 ± 0.79 and 61.4 ± 15.7 min versus 97.1 ± 38.2 min, respectively, P < 0.05).There were no statistically significant differences between both groups for the estimated blood loss, requirement of blood transfusion, complications, and future fertility. Conclusion: Laparoscopic cornual resection (cornuotomy) is a safe and less invasive procedure with a comparable complication rate. It has shown that it is feasibility and should be considered as initial treatment in managing those cases in trained hand surgeons.